The Influence of Financial Literacy, Financial Inclusion and Financial Management on MSME Performance in The East Canal Flood Area (BKT) - Caroline, Nataly; Farida; Herminda; Mahanani, Estu; Ruwaida (IKRAITH-EKONOMIKA, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, butthey face challenges in improving their performance, particularly related to financial literacy andfinancial inclusion. This study aims to investigate the relationship between financial literacy,financial inclusion, and financial management with the performance of MSMEs. Recent studiesshow that higher financial literacy and financial inclusion have a positive impact on the performanceof MSMEs. Moreover, effective financial management also significantly affects the ability ofMSMEs to access financing and improve profitability. This research concludes that improvingfinancial literacy, financial inclusion, and effective financial management are key factors insupporting the performance and sustainability of MSMEs in Indonesia.